Analisis Semiotika Pesan Ketidaksetiaan dalam Film Layangan Putus - Intan Rizky Anisa; Siti Muyasaroh; Moh. Edy Marzuki (Universitas Merdeka Malang, 2023)
The purpose of this study was to determine the message of disloyalty using the meaning of denotation, connotation, and myth contained in the film Layangan Putus. The research method used in this research is the descriptive qualitative research method which is an in-depth study. This study uses Roland Barthes' semiotic theory to analyze message signs using the meaning of denotation, connotation, and myth contained in each scene in Layangan Putus. The results of the study indicate that the film Layangan Putus represents the message of disloyalty to the figure of Aris conveyed by the film Layangan Putus. It does not only mean entertaining, but contains many moral, educational, and educational values. As for the results of some of these messages of unfaithfulness in the form of dishonest behavior that can eliminate trust in partners, infidelity can damage relationships and forms of infidelity not only by having intimate (sexual) relationships.